(-)-Englerin-A has analgesic and anti-inflammatory effects independent of TRPC4 and 5 - Sousa,Valente J; Alavi,J; Barde,S; Zarban,A; Kodji,X; That,D; Argunham,F; Barrett,B; Nagy,I; Brain,SD (International Journal of Molecular Sciences, 2021)
Recently, we found that the deletion of TRPC5 leads to increased inflammation and pain-related behaviour in two animal models of arthritis. (-)-Englerin A (EA), an extract from the East African plant Phyllanthus engleri has been identified as a TRPC4/5 agonist. Here, we studied whether or not EA has any anti-inflammatory and analgesic properties via TRPC4/5 in the carrageenan model of inflammation. We found that EA treatment in CD1 mice inhibited thermal hyperalgesia and mechanical allodynia in a dose-dependent manner. Furthermore, EA significantly reduced the volume of carrageenan-induced paw oedema and the mass of the treated paws. Additionally, in dorsal root ganglion (DRG) neurons cultured from WT 129S1/SvIm mice, EA induced a dose-dependent cobalt uptake that was surprisingly preserved in cultured DRG neurons from 129S1/SvIm TRPC5 KO mice. Likewise, EA-induced anti-inflammatory and analgesic effects were preserved in the carrageenan model in animals lacking TRPC5 expression or in mice treated with TRPC4/5 antagonist ML204.This study demonstrates that while EA activates a sub-population of DRG neurons, it induces a novel TRPC4/5-independent analgesic and anti-inflammatory effect in vivo. Future studies are needed to elucidate the molecular and cellular mechanisms underlying EA’s anti-inflammatory and analgesic effects.